Effect of Leverage, Environmental Performance, and Environmental Disclosure on Economic Performance on Natural Resources Management Industry Companies - Arief Fitriyanto (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
This study analyzes the influence of leverage, environmental performance, and environmental disclosure on economic performance in natural resources management industry companies registered in BEI. The period of research used is 5 years, namely 2014 - 2018. The population of this study includes all natural resources management industry companies registered in IDX for the period 2014-2018. Sampling techniques using purposive sampling techniques. Based on the criteria that have been set obtained 6 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is data panel regression analysis. The results showed that leverage has a significant negative effect on economic performance, and environmental performance does not have a significant influence on economic performance, while environmental disclosure has a significant positive effect on economic performance.